Clima laboral de la empresa “Abc Technology” De La Ciudad De Babahoyo. - Guerrero Loor, Stephanie Melissa (2022)
The objective of this case study is to analyze the work environment of the Abc Technology Company of the City of Babahoyo, in order to detect the sources of conflict that generates a work environment that is not conducive to the development of the company, in addition to allowing employees to employees develop their skills and abilities for the benefit of the company and provide good service to customers, causing them greater growth at the business level.